The Influence of System Quality Factors and Information Quality on The Quality of Financial Reports Using SIPD RI at BPKAD of Sulawesi Tengah Province - Nur Kholifah; Masruddin; Sugianto; Fikry Karim (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
The primary objective of this study is to evaluate and examine the influence of System Quality and Information Quality on Financial Report Quality related to the implementation of the Regional Government Information System (SIPD RI) within the Regional Finance and Asset Management Agency (BPKAD) of Central Sulawesi Province. SIPD RI serves as a centralized digital platform that supports local government activities in financial planning, budgeting, implementation, and reporting. This study employed a quantitative strategy utilizing the Structural Equation Modeling–Partial Least Squares (SEM-PLS) framework. Data collection was conducted by distributing a Likert-scale questionnaire (scored from 1 to 5) to BPKAD employees who routinely operate SIPD RI. The findings indicate that system quality and information quality have a constructive and meaningful impact on Financial Report Quality. These findings suggest that improving the performance of the system and information generated by SIPD RI can improve local government financial reporting standards. Thus, these results provide practical recommendations for local governments in optimizing the potential of SIPD RI in increasing public financial transparency and accountability.